ENHANCEMENT OF CODE DIVISION MULTIPLE ACCESS (CDMA) WITHIN THE GSM SYSTEM IN IRAQ - Nabil Abdulwahab Abdulrazaq Baban (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Despite the widespread adoption of Global System for Mobile Communications (GSM) in Iraq, the network's capacity and performance limitations have become increasingly apparent, particularly in urban areas with high user density. Currently, LTE (4G) is the dominant mobile technology in Iraq, provides faster data speeds, improved coverage, and enhanced features compared to CDMA. GSM network has still function in rural areas with low population density using GSM infrastructure as Time Division Multiple Access (TDMA), and Frequency Division Multiple Access (FDMA). This paper explores the potential of Code Division Multiple Access (CDMA) technology to enhance the GSM system in Iraq instead of TDMA, and FDMA, addressing issues such as limited capacity, interference, and inefficient spectrum utilization. This study conducted a comprehensive simulation of a GSM network integrated with CDMA technology using a state-of-the-art network simulator. The simulation was designed to evaluate the performance of the enhanced system under various traffic loads, channel conditions, and interference scenarios. The integration involved the allocation of specific frequency bands for CDMA operation, the implementation of CDMA spreading codes, and the optimization of power control mechanisms. CDMA is particularly well-suited for the GSM system in Iraq due to its inherent advantages in handling interference and managing spectrum efficiently. Unlike TDMA, FDMA, which are primarily used in GSM in Iraq, CDMA spreads the signal across a wide frequency band, making it more resilient to interference. This characteristic is especially beneficial in Iraq, where the spectrum is congested and interference levels are high. Additionally, CDMA's ability to dynamically allocate resources based on user demand ensures efficient spectrum utilization and improved capacity. The simulation results demonstrate that the integration of CDMA into the GSM system in Iraq can significantly enhance network capacity, reduce interference, and improve overall performance. The enhanced system is capable of handling higher traffic volumes, providing better quality of service for users, and supporting emerging applications that demand high data rates and low latency